Combining Effect of Lower Rate of Trifluralin Herbicide and Sunflower residues on mycorrhizal association with cowpea and soil nitrification - K. Sarbout, Ali; S. Alsaadawi, Ibrahim (Iraqi Journal of Science, 2023)
Field and laboratory experiments were conducted during the course of study totest if the sunflower residues along or with 50% full rate of trifluralin herbicide hasany impact on mycorrhizal association and soil nitrification which are importantprocesses for improving growth and productivity of crops. Results revealed thatincorporation of sunflower residues significantly increased spores number at 2, 4and 6 weeks of residue decomposition compared to control treatment. However,when the residues applied in combination with reduced rate of trifluralin herbicide,sporulation was appreciably decreased by sunflower residues at 3 t ha-1 but itremains almost the same at 6 t ha-1 rate of residues. Field soil amended with labelrate of trifluralin showed lower sporulation during the first six weeks frombeginning of the experiment. Colonization rate was appreciably increased byapplication of sunflower residues at 6 t ha-1 and decreased by label rate of herbicideand weed free treatments. The highest colonization intensity (83.4) was recorded byapplication of sunflower residues at 6 t ha-1, followed by treatment of sunflowerresidues at 3 t ha-1 (72.2). Label rate of herbicide recorded the least colonizationintensity (54.4). Incorporation of sunflower residues at 3 and 6 t ha-1 significantlyreduced nitrification rate at all incubation periods in comparison to control.However, when the residues was applied along with the reduced rate of herbicide,nitrification rate was significantly increased over the sole application of sunflowerresidues at all incubation periods except 4 and 8 days incubation periods but itremains below control. Soil sterilization treatment showed the least nitrification rateat all incubation periods. In all bioassay experiments, the amounts of NH4+convertedin the incubated soil was significantly correlated with the amount of NO3- producedover the periods of incubation suggesting that soil incubation is efficient method thatcan be used for measuring nitrification process.It can conclude Sunflower residuesamended in field soil was found to provide a good medium for growing Glomusmosseae fungus and best way to inhibited nitrification rate and thus may contributein alleviating losses of NO3 used by plants and reducing the environmentalpollution.